Imaging the electronic structure of on-surface generated hexacene. Issue 10 (19th December 2016) - Krüger, Justus; Eisenhut, Frank; Alonso, José M.; Lehmann, Thomas; Guitián, Enrique; Pérez, Dolores; Skidin, Dmitry; Gamaleja, Florian; Ryndyk, Dmitry A.; Joachim, Christian; Peña, Diego; Moresco, Francesca; et al.
Abstract : Hexacene put on the map: on-surface reduction of precursors pushes the boundaries set by stability and allows single molecule investigation. Abstract : Surface-assisted reduction of specially designed air-stable precursors allows us to study single hexacene molecules on Au(111) by scanning tunneling microscopy and spectroscopy, mapping with intramolecular resolution their extended electronic eigenstates.